Improved weighting scheme using consumer-level GNSS L5/E5a/B2a pseudorange measurements in the urban area. Issue 7 (1st October 2020) - Ng, Hoi-Fung; Zhang, Guohao; Yang, Kai-Yuan; Yang, Shi-Xian; Hsu, Li-Ta
Highlights: Weight scheme for GNSS L1/L5 band measurements. Outlier exclusion based on the features derived from dual-frequency measurements. L1/L5 band consistency check to mitigate multipath/non-line-of-sight effects. Assessments of GNSS L5/E5a/B2a in Asian urban canyon. Abstract: The accurate global navigation satellite system (GNSS) positioning in the dense urban areas is still a challenge, especially for low-cost receivers. The multipath effects and non-line-of-sight (NLOS) receptions from surrounding buildings will significantly degrade the positioning performance. Due to the increasing channel number in GNSS chip, the low-cost receiver tends to be capable of acquiring multi-frequency signals, including the new L5-band signal. Because of the higher chipping rate, the GNSS L5-band measurement is less affected by the multipath effect, whereas the measurement number is limited in the current stage. On the contrary, the availability of the conventional L1-band measurement is sufficient to achieve a good dilution of precision (DOP). Based on the complementary characteristics, a GNSS L1/L5 bands integrated positioning algorithm is developed in this study to improve the positioning performance in urban areas. A modified weighting model based on carrier-to-noise ratio and satellite elevation angle is employed to assign proper weighting between L1-band and L5-band measurements. Meanwhile, the dMP5 feature from dual-frequency measurement and the consistency check algorithm are employed to detect and exclude outliers, which are possibly NLOS receptions. Experimental results and analyses indicate that the developed DFE-CCWLS method can significantly improve the positioning accuracy, achieving the root-mean-square error less than 10 m for most of the urban scenarios.